Environmental Interpretation - Sumarjono Soedargo; E.K.S Harini Muntasib; Dones Rinaldi (Media Konservasi, 1989)
Environmental Interpretation is one kind of services for the natural park area visitors, that can bridge between the visitors and the environmental and natural resources. The interpretation services include information service, educational service, inspiration service and propaganda. Interpretation programs are expected to develop the knowledge and understanding of the visitors about natural resources and hence, to develop the conscious and wise behaviour toward natural conservation.